Injury and not the pathogen is the primary cause of corm rot in Crocus sativus (saffron) - Mansotra, Ritika; Ali, Tahir; Bhagat, Nancy; Vakhlu, Jyoti (Frontiers in Plant Science, 2023)
Fusarium oxysporum has been reported to be the most devastating pathogen of the Crocus sativus L., a commercially significant crop, that yields the saffron spice. However, most of the pathogen isolations have been done from the diseased tissue, mostly from rotten corms but no study has been conducted on diseased saffron fields. To fill the knowledge gap, the current study was carried out with the intention of recording the diversity of cultivable fungus species from saffron fields and screening them for pathogenicity towards saffron. The three study locations in Jammu and Kashmir, Srinagar (Pampore), Kishtwar, and Ramban, yielded a total of 45 fungal isolates. Internal transcribed spacer (ITS) of rDNA was used for the molecular identification. ITS rDNA based sequence analysis classified all the operational taxonomic units (OTUs) into two phyla- Ascomycota (88.88%) and Mucoromycota (11.11%). Moreover, Fusarium (57.77%), Geotrichum (17.77%), Mucor (11.11%), Aspergillus (4.44%), Trichoderma (4.44%), Galactomyces (2.22%), and Colletotrichum (2.22%), all had different total abundances at the genus level. It was discovered that the saffron fields in Srinagar has fewer varied fungal species than the other two selected sites. All of the fungal isolates isolated including Fusarium solani, Aspergillus flavus, Trichoderma harzianum, Fusarium neocosmosporiellum, Mucor circinelloides, etc. were pathogenic according to the pathogenicity test; however injury to the saffron plant was found to be must. These fungi were pathogenic in addition to Fusarium oxysporum, which is well documented as major cause of saffron corm rot diseases in Srinagar, but in present study injury was must for Fusarium oxysporum as well. The percentage disease severity index for both saffron roots and corms varied for each fungal isolate.